The glamour of strangeness artists and the last age of the exotic - James, Jamie (Farrar, Straus and Giroux, 2016)
"Exploration of a "rare, emotionally intense way of life" in which artists like Raden Saleh and Walter Spies abandon the cultures that created them and adopt an exotic alternative"--
Includes bibliographical references (pages 325-341) and index
Keywords: Geschichte; Artists / Psychology; Artists / Biography; Alienation (Social psychology); Identity (Psychology); TRAVEL / Special Interest / Literary; BIOGRAPHY & AUTOBIOGRAPHY / Artists, Architects, Photographers; ART / History / Modern (late 19th Century to 1945); Artists; Künstler; Exotik; Biografie